[9] α-Blockers and acute urinary retention - Samir Bouras (Taylor & Francis Group, 2018)
Objective: To evaluate the effect of α-blockers in patients with acute urinary retention (AUR), as lower urinary tract symptoms (LUTS) are a common pathology in men and AUR is an emergency requiring urgent catheterisation in order to pass this phase and recover spontaneous urination after trial without catheter (TWC). Methods: This prospective cohort study included 77 patients who underwent bladder catheterisation for AUR, from April 2017 to March 2018. The protocol consisted of studying epidemiological characteristics, data concerning LUTS, and the impact of α-blockers on the TWC. We randomised patients into three groups: a TWC immediately, an appointment at 48 h and 72 h. Results: The mean (range) age was 70.2 (45–96) years. Most patients presented for a first episode f AUR. The digital rectal examination was suggestive of adenoma in 61 (77.9%) patients and 51 (66.2%) had no treatment. A TWC immediately without treatment was performed in seven of 77 patients (9.1%), and 49 (63.6%) received an α-blocker alone or combined with other drugs. Only 65 (84.4%) patients answered the test, and many of them did not respect the given dates. Three of four patients were positive to immediate TWC (no AUR within 24 h after ablation), nine of 14, seven of 10, and two of nine were positive, for the 48 h, 72 h, and ⩾10 days groups, respectively. There was no statistically significant difference (P >  0.005) comparing the groups response to TWC according to the treatment modalities, as well as for the study duration. Even when we chose alfuzosin 10 mg and compared it with other medications, there was no significance. However, the use of antibiotic prophylaxis was a predictor of a positive TWC (P = 0.021). Conclusion: Many well-designed studies have confirmed the role of α-blockers in increasing the chances of a successful TWC. However, in the present study there was no evidence that α-blockers are more efficient than other treatments, our study has several limitations and it should to be expanded and further research is needed.